PARTITIONING OF ELEMENTS AMONG TWO SILICATE PEROVSKITES, SUPERPHASE B, AND VOLATILE-BEARING MELT AT 23 GPA AND 1500-1600°C - Gasparik T.; Drake M.J. (My University, 1995)
The partitioning of Si, Mg, and Ca in major concentrations, and Al, Ti, Sc and Sm in minor concentrations among MgSiO3 perovskite, CaSiO3 perovskite, superphase B -Mg10Si3O14[OH,F]4, and melt containing H2O and fluorine, was determined experimentally at 23 GPa and temperatures of 1500-1600°C with a split-sphere anvil apparatus (USSA-2000). MgSiO3 perovskite is the main repository for Sc, while Ti and Sm are primarily concentrated in CaSiO3 perovskite. Superphase B excludes all cations other than Mg and Si, except at high volatile contents of the melt when Ti and Al become compatible. Volatile-bearing melt is conspicuous by its high Mg content and low content of all other cations. This observation raises the possibility that the Mg ratio of the Earth's upper mantle, which is elevated relative to most classes of primitive meteorites, was established by upward segregation of Mg-rich volatile-bearing melts from the lower to upper mantle. The most plausible scenario involves degassing of the lower mantle by removal of 6% of the melt produced by a low degree of partial melting. The possibility that the elevated Mg ratio of the upper mantle could have resulted from upward segregation of residual Mg-rich volatile-bearing melts from a terrestrial magma ocean has been evaluated and shown to be unlikely. If the Earth ever had a magma ocean, it seems more probable that the elevated Mg ratio of the observable upper mantle is either characteristic of the entire silicate portion of the planet, or that the magma ocean was limited in depth to the upper mantle.